More green thoughts than actions: Insights from marketing instructors at a Canadian University - Anh Thu Nguyen; Paul Berger; Ellen Field (Cleaner and Responsible Consumption)
Sustainability discourse provides directions for sustainable development in the global context; education should be transformed to address sustainability concerns. Many universities have adopted a sustainability focus and university instructors play a vital role in inculcating sustainability principles in students, but in business education there is little research on how marketing instructors interpret sustainability or how that affects their teaching. This qualitative case study used semi-structured interviews and content analysis of course syllabi to gain the insights of marketing instructors at a university in Canada; specifically, how they interpret sustainability, how they integrate sustainability into their marketing instruction, and the perceived factors affecting their teaching practices. Thematic analysis with NVivo identified a dilemma; business worldviews limit what marketing instructors think about sustainability and whether and how they teach it in marketing courses. If marketing instructors are not teaching about sustainability, it is a missed opportunity to transform production, consumerism and marketing. As universities are increasingly trying to implement sustainability integration in teaching and learning, this research provides useful implications for marketing instructors, educational leaders, business schools, professional associations and textbook publishers.